-6x-5y=1

Simple and best practice solution for -6x-5y=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x-5y=1 equation:


Simplifying
-6x + -5y = 1

Solving
-6x + -5y = 1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5y' to each side of the equation.
-6x + -5y + 5y = 1 + 5y

Combine like terms: -5y + 5y = 0
-6x + 0 = 1 + 5y
-6x = 1 + 5y

Divide each side by '-6'.
x = -0.1666666667 + -0.8333333333y

Simplifying
x = -0.1666666667 + -0.8333333333y

See similar equations:

| 4+3y-3y=4 | | 9n+68=7n+2n-2 | | 0=-4-4x-3x^2 | | 19+(-4y)+4y=19 | | 9x+1=3x-7 | | 9x+1=3x-1 | | 3(4+-2y)+4y=10 | | Y=-4/7x-1/7 | | 15x^2+40x-5=0 | | log(x)=0.40338 | | n^2-12n+21=0 | | e^8-9x=1168 | | 1/3(9)cubed | | 3/x-12/x-3=1 | | X^2+x+121=0 | | 230/360 | | 11/2×e=6 | | (2x+4)(2x+8)(x*x+4)=0 | | x^2-26y+169=0 | | 8x-12-3+3x-21=4.5 | | 4=0.5x+30 | | 30=0.5x+4 | | x(x+2)=7(x+x+2)+71 | | (2x+y)(3x+5y)= | | 15x^2+10=0 | | -4.5q+1.7=-25.8-2q | | 4x^2-23x-11=0 | | (b-8)/(8b-16) | | 8x-12+3x-21=4.5 | | S=5k+5vfork | | 4(1+3n)=8(n+5) | | 3p^2+10p+8=0 |

Equations solver categories